2021
DOI: 10.1186/s12877-021-02141-w
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and associated factors of polypharmacy in older patients in primary care: a northern Italian cross-sectional study

Abstract: Background A precondition for developing strategies to reduce polypharmacy and its well-known harmful consequences is to study its epidemiology and associated factors. The objective of this study was to analyse the prevalence of polypharmacy (defined as ≥8 prescribed drugs), of potentially inappropriate medications (PIMs) and major drug-drug interactions (DDIs) among community-dwelling general practice patients aged ≥75 years and to identify characteristics being associated with polypharmacy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 54 publications
1
17
0
5
Order By: Relevance
“…In both treatment groups, quality of life and affective status showed a tendency to decrease over time, most probably due to the natural functional decline in older-aged patients. Interestingly, the cognitive function of the assessed participants remained stable throughout the observation period which concords to the fact that only few patients with diagnosticated dementia participated in the study [ 31 ] and severe cognitive impairment was an exclusion criterium.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In both treatment groups, quality of life and affective status showed a tendency to decrease over time, most probably due to the natural functional decline in older-aged patients. Interestingly, the cognitive function of the assessed participants remained stable throughout the observation period which concords to the fact that only few patients with diagnosticated dementia participated in the study [ 31 ] and severe cognitive impairment was an exclusion criterium.…”
Section: Discussionmentioning
confidence: 96%
“…This northern-Italian RCT investigated the effect of medication reviews and recommendations provided by three experts with different professional background on patient-relevant outcomes in older-aged general practice patients on polypharmacy. The study found a high prevalence of polypharmacy, PIMs and DDIs, as described in the publication of epidemiological baseline data [ 31 ]. The composite primary outcome of non-elective hospital admissions or death was experienced significantly more often in the IG in the unadjusted analysis; yet, as significance disappeared after adjustment, which was also noted for hospitalisations as single secondary endpoint, this phenomenon seems to be strongly related to the higher occurrence of hospital admissions in the IG within the pre-interventional period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, depression may have played a crucial role as it is considered one of the most important risk factors for suicide, especially in older adults [ 28 ], and is also an independent risk factor for excessive polypharmacy [ 29 ]. Furthermore, antidepressants are one of the most common contributors of polypharmacy and, when present, they are the second most frequently interacting drug [ 30 ]. We detected higher poisoning suicide mortality among older adults living in urban rather than rural areas, a finding that could be linked to the overall higher prevalence of depression in urban environments [ 31 ].…”
Section: Discussionmentioning
confidence: 99%